2023
DOI: 10.3390/plants12091876
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotime Model Parameters Estimate Seed Vigor and Predict Seedling Emergence Performance of Astragalus sinicus under Various Environmental Conditions

Abstract: Seed vigor is an important aspect of seed quality. High-vigor seeds show rapid and uniform germination and emerge well, especially under adverse environmental conditions. Here, we determined hydrotime model parameters by incubating seeds at different water potentials (0.0, −0.2, −0.4, −0.6, and −0.8 MPa) in the laboratory, for 12 seed lots of Chinese milk vetch (Astragalus sinicus) (CMV), a globally important legume used as forage, green manure, and a rotation crop. Pot experiments were conducted to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Thus, any differences in their germination and emergence patterns and stress resistance were not due to their genotype. Therefore, the differences in the lag period of delay to germination are most likely due to their actual vigor level caused by seed aging or deterioration [9]. We noticed that in our study, among all seed lots, as expressed by seedling emergence under field and pot conditions, seed lots 6, 10, and 11 had relatively high vigor and were also the youngest of all seed lots (stored one or two years before the experiment); on the other hand, seed lots 8 and 13, had the lowest vigor level (longer MGT or lower seedling emergence under different conditions) and was also the oldest of all seed lots (stored five years before the experiment).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, any differences in their germination and emergence patterns and stress resistance were not due to their genotype. Therefore, the differences in the lag period of delay to germination are most likely due to their actual vigor level caused by seed aging or deterioration [9]. We noticed that in our study, among all seed lots, as expressed by seedling emergence under field and pot conditions, seed lots 6, 10, and 11 had relatively high vigor and were also the youngest of all seed lots (stored one or two years before the experiment); on the other hand, seed lots 8 and 13, had the lowest vigor level (longer MGT or lower seedling emergence under different conditions) and was also the oldest of all seed lots (stored five years before the experiment).…”
Section: Discussionmentioning
confidence: 99%
“…Despite SWR's valuable agricultural and ecological uses and economical importance, its low seed yield and quality have become one of the major constraints encountered by farmers, herders, and agricultural companies. Previous research suggested that poor establishment of small-seeded forage species is common, and weak seedlings produced by forage seeds also reduce the possibility of survival [7,8], especially under adverse environmental conditions, such as drought, salinity, and alkalinity stresses [9]. Thus, improving stand establishment in unfavorable environmental conditions is a critical determinant of SWR cultivation and utilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrotime model provides useful information on seed germination characteristics under stress conditions, defining the tolerance or sensitivity of a variety to salt stress [43]. Its parameters are hydrotime requirements (θ H ), which define the speed of germination, and base water potential (Ψ b ), which indicates the minimum potential (Ψ) of a seed lot to reach germination.…”
Section: Discussionmentioning
confidence: 99%